Stress Distribution on Bone Due to Dental Implant - Ajay Gaikwad; Lishoy W Rodrigues; Karuna Gajanan Pawashe; Praveen Gangadharappa; Amit Bajirao Jadhav; Shruti Dabi (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The distribution of stress (DS) in the bone around dental implant (DI) during loading is associated with success. In contrast, upon loosening of DI because of high stress, leads to its failure. Aim: To evaluate the DS for single and multi-rooted RAI using the photo elastic (PE) method. Material and Method: In our study, we have included extracted teeth of the maxillary central incisor, and mandible 1st molar for RAI fabrication into 3 different phases out of which one was photoelastic stress analysis. Result: We found fringe on both sides at cervical region for titanium (Ti) and highest for molar than incisor for Zirconium (Zr) and Polyetheretherketone (PEEK). Conclusion: PE analysis is unable to include the forces exerted by the surrounding muscles, as well as the impact of various forces during a chewing cycle.